Involvement of 2'-5' oligoadenylate synthetase-like protein in the survival of Mycobacterium tuberculosis avirulent strain in macrophages - Aikebaier Reheman; Xiaojian Cao; Yifan Wang; Xi Nie; Gang Cao; Wei Zhou; Bing Yang; Yingying Lei; Weipan Zhang; Muhammad Ahsan Naeem; Xi Chen (BMC, 2023)
Abstract Mycobacterium tuberculosis (M. tuberculosis) can replicate in the macrophage by interfering with many host protein functions. While it is far from known these host proteins for controlling M. tuberculosis infection. Herein, we infected macrophages including THP-1 and Raw264.7 cells with M. tuberculosis and identified the differentially expressed genes (DEGs) in the interferon signaling pathway. Among them, 2'-5' oligoadenylate synthetase-like (OASL) underwent the greatest upregulation in M. tuberculosis-infected macrophages. Knockdown of the expression of OASL attenuated M. tuberculosis survival in macrophages. Further, bioinformatics analysis revealed the potential interaction axis of OASL-TAB3- Rv0127, which was further validated by the yeast-two-hybrid (Y2H) assay and Co-IP. This interaction axis might regulate the M. tuberculosis survival and proliferation in macrophages. The study reveals a possible role of OASL during M. tuberculosis infection as a target to control its propagation.